Probing protoneutron stars with gamma-ray axionscopes - Lella, Alessandro; Calore, Francesca; Carenza, Pierluca; Eckner, Christopher; Giannotti, Maurizio; Lucente, Giuseppe; Mirizzi, Alessandro (Journal of cosmology and astroparticle physics, 2024)
Axion-like particles (ALPs) coupled to nucleons can be efficiently produced in the interior of protoneutron stars (PNS) during supernova (SN) explosions. If these ALPs are also coupled to photons they can convert into gamma rays in the Galactic magnetic field. This SN-induced gamma-ray burst can be observable by gamma-ray telescopes like Fermi-LAT if the SN is in the field of view of the detector. We show that the observable gamma-ray spectrum is sensitive to the production processes in the SN core. In particular, if the nucleon-nucleon bremsstrahlung is the dominant axion production channel, one expects a thermal spectrum with average energy E a ≃ 50 MeV. In this case the gamma-ray spectrum observation allows for the reconstruction of the PNS temperature. In case of a sizable pion abundance in the SN core, one expects a second spectral component peaked at E a ≃ 200 MeV due to axion pionic processes. We demonstrate that, through a dedicated LAT analysis, we can detect the presence of this pionic contribution, showing that the detection of the spectral shape of the gamma-ray signal represents a unique probe of the pion abundance in the PNS.